2014
DOI: 10.1097/pai.0000000000000012
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Expression of HIF-α Plays a Major Role in Generation of Clear-cell Phenotype in Human Primary and Metastatic Renal Carcinoma

Abstract: The extensive lipid accumulation occurred in clear cell renal cell carcinoma (ccRCC) resulted in a clear cell cytoplasm. Hypoxia inducible factor alpha (HIF-α) was constitutively expressed in many ccRCC and transcriptionally regulates greater than one hundred genes. In a recent breakthrough study, HIF-1α induced ccRCC in transgenic mice. Based on these findings, we developed a hypothesis that accounted for HIF-α generation of the clear cell phenotype. The aim of the present study to use immunohistochemical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…There is an unmet clinical need to identify a new treatment modality that is patient-centric, selective, and efficacious for metastatic ccRCC patients. Both primary and metastatic ccRCC tumors are uniquely characterized by the expression of altered biomarkers associated with increased angiogenesis, metastasis, and drug resistance, including deletion and/or mutation of the von Hippel–Lindau (VHL) tumor suppressor gene in the majority of ccRCC tumors, resulting in the stable expression of hypoxia-inducible factors 1α and 2α (HIFs), and vascular endothelial growth factor (VEGF) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Programmed death 1 (PD-1) is expressed in the membrane and cytoplasm of activated T cells, B cells, and dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…There is an unmet clinical need to identify a new treatment modality that is patient-centric, selective, and efficacious for metastatic ccRCC patients. Both primary and metastatic ccRCC tumors are uniquely characterized by the expression of altered biomarkers associated with increased angiogenesis, metastasis, and drug resistance, including deletion and/or mutation of the von Hippel–Lindau (VHL) tumor suppressor gene in the majority of ccRCC tumors, resulting in the stable expression of hypoxia-inducible factors 1α and 2α (HIFs), and vascular endothelial growth factor (VEGF) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Programmed death 1 (PD-1) is expressed in the membrane and cytoplasm of activated T cells, B cells, and dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Better understanding of the pathophysiology of clear cell RCC (ccRCC) in recent years has shown the important role of HIF-1α pathways [10,11], which has led to successful application of antiangiogenic drugs targeting VEGF [12] and has promoted the use of other related markers such as carbonic anhidrase-9 as prognostic markers [13]. Thus, HIF-1α and its downregulated genes have an important role in the pathophysiology of both OSA and ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…Under hypoxia, the enzymatic activity of PHDs decreases, resulting in a decreased hydroxylation and degradation of HIFs. Unlike in many solid tumors, ccRCC tumors, at initial diagnosis, are normoxic, highly vascular and express high levels of HIFs [ 8 , 16 , 17 ]. With the recognition that HIFs are upregulated by both hypoxia-dependent and independent pathways and play a crucial role in dug resistance and angiogenesis, a number of HIFs inhibitors are currently under clinical development.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in our laboratory have demonstrated that HIF1α and HIF2α proteins are overexpressed in 92% of primary ccRCC, 27% in colorectal, and 38% in head and neck tumors [ 16 , 17 ]. In contrast, VEGF-A was expressed in 54%, 79%, and 97% of ccRCC, colorectal, and, head and neck tumors, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation